2014
DOI: 10.4067/s0718-33052014000200008
|View full text |Cite
|
Sign up to set email alerts
|

Design method for a Historical Data Warehouse, explicit valid time in multidimensional models

Abstract: RESUMENPresentamos una nueva estructura de almacenamiento que denominamos DW Histórico y que contiene, explícitamente, el tiempo válido. Nuestra propuesta combina, en un modelo integrado, una Base de Datos Histórica y un DW. El objetivo del modelo propuesto es resolver las limitaciones temporales de las estructuras multidimensionales tradicionales. Aunque el DW Temporal considera, además de la dimensión temporal, otros aspectos vinculados con el tiempo, este modelo solo contempla los cambios que se producen en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In contrast, Beggar et al [14] suggested a method that uses QVT relations to create a multidimensional model from user requirements. The generation of the final code and PSM model was not explained by the authors, and in a previous study [15] used the MDA approach to create a data warehouse that allows them to store temporal structures associated with time-varying dimension levels. The authors identified the transformation rules to generate the SQL code to create the associated tables and the historical data warehouse.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast, Beggar et al [14] suggested a method that uses QVT relations to create a multidimensional model from user requirements. The generation of the final code and PSM model was not explained by the authors, and in a previous study [15] used the MDA approach to create a data warehouse that allows them to store temporal structures associated with time-varying dimension levels. The authors identified the transformation rules to generate the SQL code to create the associated tables and the historical data warehouse.…”
Section: Related Workmentioning
confidence: 99%
“…However, the code generation was not addressed. In literature, the authors used the MDA approach to generate a historical DW that allows storing temporal structures related to dimension levels varying in time. The authors defined a set of QVT transformations to generate the final model of the historical DW and the SQL code to create the associated tables.…”
Section: Related Workmentioning
confidence: 99%
“…None of these methods offer a significant automation level based on knowledge temporal constraints, source temporal structure and source temporal data. Interesting representations are given in [39] and [48]. As it stands, R2 is partially satisfied.…”
Section: R2 -Sound Temporal Schemamentioning
confidence: 99%